High and unique carbonic anhydrase activity of Photosystem II from Pisum sativum Measurements by a new and very sensitive fluorescence method - Shitov, Alexandr V (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.